Study of coronal mass ejections and their corresponding interplanetary structures using combined observations of cosmic ray detectors and coronagraphs - Carlos Roberto Braga (2015)
This Thesis aims to study coronal mass ejections (CMEs) and their interplanetary counterparts (ICMEs) using remove sensing observations from the solar corona, interplanetary in situ data and observations from ground-based cosmic ray detectors. CMEs have a central role on the Sun-Earth relationships because they are one of the main sources of geomagnetic disturbances. We have started the analysis by using a list of magnetic clouds (MCs) observed in the Earth-vicinity from 2008 to 2011. After probing the interplanetary structure, we identified the CMEs ejected in appropriate time and direction to produce each magnetic cloud. The CME propagation directions were studied thanks to the simultaneous observations of the solar corona from three viewpoints: one from the LASCO (Large Angle and Spectroscopic Coronagraph) and two others from SECCHI (Sun Earth Connection Coronal and Heliospheric Investigation). We developed a new methodology to track the CMEs in 3D combining pseudo-automatic tracking by texture with triangulation and tie-pointing analysis. For each CME analyzed, we estimated the tridimensional speed (magnitude and direction) using the new method and compared the results with previous works. Combining observations of four ground-based cosmic ray (muon) detectors, we deduced the cosmic ray density gradient during each magnetic cloud period and the overall position of the MC center. In some cases, we fit a model of cosmic ray distribution inside magnetic clouds to the observed data and deduced further properties of the MCs, such as orientation and diameter. Finally, for each case, the results derived in the solar corona were compared with those derived from cosmic ray observations.